An existence result for a class of nonlinear integral equations of fractional orders - Agarwala, Ravi P. P.; Samet, Bessem (Nonlinear Analysis: Modelling and Control, 2016)
Using a measure of non-compactness argument, we study in this paper the existence of solutions for a class of functional equations involving a fractional integral with respect to another function. Some examples are presented to illustrate the obtained results.
Keywords: integral equation; fractional; measure of non-compactness; Darbo's theorem